2018
DOI: 10.3390/app8091705
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cavity Vacuum Pressure Diminution on Thermal Performance of Triple Vacuum Glazing

Abstract: Featured Application: Triple Vacuum glazing is regarded as a smart window technology and a robust solution of retrofitting it to existing buildings for the reduction of demand side carbon emissions and improving the energy efficiency of buildings.Abstract: Long-term durability of the vacuum edge seal plays a significant part in retrofitting triple vacuum glazing (TVG) to existing buildings in achieving progress towards a zero-energy building (ZEB) target. Vacuum pressure decrement with respect to time between … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…In this paper, the vacuum laser sealing method is used to test the deposited glass, which belongs to the field of powder sintering in a vacuum environment. At present, the origin of pores and cracks in powder sintering in a vacuum environment mainly includes: residual gas between powder particles or on the surface of matrix, volatilization of impurities, and the size and distribution of the solder particles [17][18][19][20]. Because the sealing temperature of the solder is not enough, the pores cannot overflow from the melting layer, and the viscosity of the solder decreases, which leads to a large number of blocky structures.…”
Section: Formation Mechanism Of Pores In Vacuum Glass Sealing Layer Bmentioning
confidence: 99%
“…In this paper, the vacuum laser sealing method is used to test the deposited glass, which belongs to the field of powder sintering in a vacuum environment. At present, the origin of pores and cracks in powder sintering in a vacuum environment mainly includes: residual gas between powder particles or on the surface of matrix, volatilization of impurities, and the size and distribution of the solder particles [17][18][19][20]. Because the sealing temperature of the solder is not enough, the pores cannot overflow from the melting layer, and the viscosity of the solder decreases, which leads to a large number of blocky structures.…”
Section: Formation Mechanism Of Pores In Vacuum Glass Sealing Layer Bmentioning
confidence: 99%
“…A 1 (m 2 ) refers to the radiative area. C (5.67 × 10 −8 W/(m 2 •K 4 )) refers to the Stefan-Boltzmann constant [23]. T 1 and T 2 (K) are the environment temperature and the temperature of the radiative face.…”
Section: Conductive Heat Transfer Processmentioning
confidence: 99%
“…To increase the work temperature, the influence of the sealing agent width, view size, and vacuum thermal conductivity on the temperature of the organic glass was studied, because these factors directly affect the heat transmission [23,24]. Results show that the vacuum multiple glass has a good heat insulation and can work in the high temperature of 170 ℃, which is higher than the allowable temperature of 120 ℃ for the organic glass, and the neutron heat: = 1E5 × exp (−x/0.01) Wm -3 .…”
Section: Effect Of the Work Temperature On The Temperature Distributimentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the performance of a vacuum-glazed window varies depending on the magnitude of the vacuum pressure. Memon et al [18] verified the thermal performance of TVG according to the magnitude of the vacuum pressure and found that the thermal performance of a vacuum-glazed window is significantly affected by the magnitude of the vacuum pressure. They determined that the total U-values of center-of-glazing and the TVGs were 0.28 and 0.94 W/m 2 K, respectively, when the vacuum pressure was 0.001 Pa; however, those values became 2.4 and 2.58 W/m 2 K when the pressure was 100 kPa (atmospheric pressure).…”
Section: Performance Of Vacuum-glazed Windowsmentioning
confidence: 99%